Mitigating Motion Sickness by Anticipatory Cues - Anna J. C. Reuten; Jelte E. Bos; Marieke H. Martens; Jessica Rausch; Jeroen B. J. Smeets (Vibration, 2024)
Car passengers suffer much more from motion sickness compared to car drivers, presumably because drivers can better anticipate the car’s motions. Visual and auditory cues that announce upcoming motions have been demonstrated to mitigate motion sickness. In automated vehicles, vibrotactile cues might be more desirable. However, prior studies provided mixed evidence regarding their effectiveness. In this study, we directly compared the effectiveness of anticipatory auditory and vibrotactile cues. We determined their effectiveness by examining self-reported motion sickness from anticipatory sessions with auditory or vibrotactile cues announcing the onset and direction of upcoming motion relative to a control session. Our preregistered analysis did not show a significant difference in mitigation between the cues but also no significant overall effect. As this lack of an effect may be due to limited statistical power, we performed an internal meta-analysis. This analysis demonstrated a small overall effect of anticipatory cues. We conclude that it is worthwhile to investigate how their effectiveness can be enhanced.